2021
DOI: 10.1002/joc.7062
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of the responses of soil temperature and soil moisture to climate change over the Tibetan Plateau, 1961–2010

Abstract: Changes in soil temperature (ST) and soil moisture (SM) are essential for climate change and ecosystem assessments. Previous investigations on the ST and SM on the Tibetan Plateau (TP) are mainly based on the situ observation and the satellite products. In this study, the improved Community Land Model version 4.5 (CLM4.5), with proper parameter optimization and surface datasets update, is used to estimate the response of ST and SM in the TP to climate change in the long‐term time series from 1961 to 2010. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…Figure 1d shows that the conversions from permafrost into SFG was prevailing across the entire QTP, especially in the southern QTP. The shortens of freezing and thawing duration in active layer in the 1990s is likely to cause permafrost more vulnerable to climate change, which coincides with previous results [39]. Our results indicated that, in contrast to 1990s, an area counting 33.33 % of permafrost on the QTP thawed into SFG in 2000s.…”
Section: Decadal Changes Of Permafrost Distribution On the Qtp From 1...supporting
confidence: 90%
See 2 more Smart Citations
“…Figure 1d shows that the conversions from permafrost into SFG was prevailing across the entire QTP, especially in the southern QTP. The shortens of freezing and thawing duration in active layer in the 1990s is likely to cause permafrost more vulnerable to climate change, which coincides with previous results [39]. Our results indicated that, in contrast to 1990s, an area counting 33.33 % of permafrost on the QTP thawed into SFG in 2000s.…”
Section: Decadal Changes Of Permafrost Distribution On the Qtp From 1...supporting
confidence: 90%
“…Moreover, the reliabilities of air temperature and precipitation components of the dataset have also been confirmed using the observational records on the QTP, prior the numerical simulation [39]. Additionally, the in-situ observations across the QTP also confirmed the simulation ability of the CLM4.5 to reproduce the soil temperature values in a long run [36,39], which were used to calculate the ground freezing/thawing indices (GFI/GTI) in this study. Meanwhile, the air freezing/thawing indices (AFI/ATI) presented in this study were also calculated using the near-surface (2 m above the ground) atmospheric temperatures derived from this data set.…”
Section: Land Surface Model Datasupporting
confidence: 70%
See 1 more Smart Citation
“…Therefore, we replaced this data set with a new soil property data set released by Beijing Normal University (hereafter referred to as the BNU data set, Shangguan et al, 2013). Fang et al (2021) compared these two datasets and demonstrated that the BNU data set can better describe the soil characteristics of the TP. We used the soil loam, clay, and sand contents from this data set and soil pedo-transfer functions (Saxton & Rawls, 2006) provided in the model to convert these content values to the soil parameters required for the model simulations.…”
Section: Model Inputmentioning
confidence: 99%
“…To drive CLM4.5 from 1979 to 2010, atmospheric datasets of high resolution (temporal of 3 hourly and spatial of 1 km) were used in this study. Observations were collected from nearly 700 stations over China (Li et al, 2014), and their reliability and the model outputs, including soil temperature and soil moisture, have been validated seriously using in-situ observations across the TP (Fang et al, 2021). More detailed information about the atmospheric datasets can be found in the website (http://globalchange.bnu.edu.cn/research).…”
Section: Observational Data and Land Surface Model Datamentioning
confidence: 99%